2020
DOI: 10.1177/0194599820954137
|View full text |Cite
|
Sign up to set email alerts
|

Timing the First Pediatric Tracheostomy Tube Change: A Randomized Controlled Trial

Abstract: Objective The first pediatric tracheostomy tube change often occurs within 7 days after placement; however, the optimal timing is not known. The primary objective was to determine the rate of adverse events of an early tube change. Secondary objectives compared rates of significant peristomal wounds, sedation requirements, and expedited intensive care discharges. Study Design Prospective randomized controlled trial. Setting Tertiary children’s hospital between October 2018 and April 2020. Methods A randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It is important to note that some studies 8,12 advocate early changes as they have been shown to decrease the length of ICU and hospital stays. However, it is not within the practices of our institution to wait for the first change for patients to be transferred or discharged.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that some studies 8,12 advocate early changes as they have been shown to decrease the length of ICU and hospital stays. However, it is not within the practices of our institution to wait for the first change for patients to be transferred or discharged.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have focused on the first tracheostomy tube change in pediatric patients [ 12 ]. In most studies, the first tracheostomy tube is changed within approximately 2–4 days, and there are no respiratory complications, wound problems, and healing; thus, an early replacement was recommended [ [9] , [10] , [11] , 13 ]. However, there may be differences in wound healing between adults and pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The post-procedural pulmonary complications increased as the first tube change was delayed. In the case of delayed tracheostomy tube change, reports have demonstrated that complications increase due to the contamination of the tube strap and delayed detection of wound problems [ 10 , 11 ]. However, in this study, post-procedural pulmonary complications were determined only with the presence or absence of abnormal findings on the formal reading such as pneumothorax, emphysema, respiratory infection, pneumonia, aspiration pneumonitis, atelectasis, tracheal stenosis, and bronchospasm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations